# bobpursly,

posted by .

Is this correct now after i revised it

Multiply. 3xy^2(5xy-4x+6y)

3xy^2(5xy)=15x^2y^3
3xy^2(-4x)=-12x^2y^2
3xy^2(6y)=18xy^3

so i get from this

15x^2y^3-12x^2y^2+18xy^3

correct

awsome i just thought that the 15x^2y^3-12x^2y^2 should be combine...

## Similar Questions

1. ### math,correction

Can someone correct these for me please... Multiply. (x+2)(x-2) My answer..x^2-4 Write in descending-exponent form, and give the degree 4x^5+x^8-7 My answer: In descending-exponent form would be: x^8+4x^5-7, The degree is 8 Multiply. …
2. ### algbrea

3x-5(3x-7)= 2(x+9) + 45 3x-15x+35= 2x+18 +45 -12x + 35 = 2x+63 -12x -28 = 2x -12 -28 =x -40 =x 3x-5(3x-7)= 2(x+9) + 45 3x-15x+35= 2x+18 +45 -12x + 35 = 2x+63 -10x+35=63 -10x=28 x=-2.8 you are both wrong! 3x - 15x + 35 = 2x + 18 + 45 …
3. ### Math

Can you correct the errors? 4(x+3)=24 4(3x)=24 12x=24 12x/12= 24/12 X=2 5(x+2)=45 5x+10=45 15x=45 15x/15=45/15 x=3 5+4x=13 5+4x-4x=13-4x 5=9x 5/9=9x/9 5/9= x 56=8(x+3) 56=8x+24 56-24=8x+24-24 32=8x 32/32=8x/32 x=8/32 x=1/4 S/6+3=11
4. ### Derive

Find the derivative of sin(2x + 3y)= 3xy + 5y-2. I have this so far 1) cos(2x+3y) * d/dx (2x+3y)= 3xy' + 3y + 5y' 2) cos (2x+3y) * [2 + 3y']= 3xy' + 3y + 5y' 3) 3y' cos (2x+3y) + 2cos(2x+3y)= 3xy' + 3y + 5y' 4) 3xy' + 5y' - (3y(cos(3x+3y)= …
5. ### Algebra

–2x(–3x ^2y)(2y) = ? A. 12x^3y^2 B. –3xy^2 C. 3xy^2 D. –12x^3y^2
6. ### Math help polynomial

multiply the following polynomial -3x(y^2+2y^2) answer choices 3xy^2-6xy^2' -3xy^2-gxy^2 -3xy^2+5y^2 -9xy^2 The last one was the answer. Can you tell me how the answer was solved?
7. ### Math!

1) What is the value of 19 + 5a^4 + 3b^2 when a = 2 and b = -4?
8. ### algebra

Simplify. Do not use negative exponents in the answer. 12x-2y4 -3xy-7 There should be a line between like a fraction but it did not copy or paste. This is the answer I got 12 x^-2 y^4 = 12y^4/x^2 -3xy^-7 = -3x/y^7 it was wrong. 12x^-2y^4 …
9. ### Simultaneous equation

X+y+z=1......(1) x^2+y^2+z^2=35........(2) x^3+y^3+z^3=97.........(3) solution but from 3 (x^3+y^3)=(x+y)^3-3xy(x+y)......(4) puting 4 into 3 bck (x+y)^3-3xy(x+y)+z^3=97.......(5) now from 1 x+y=1-z......(6) putin 6 into 7 we have …
10. ### polynomials

I have to simplify (-x^5y^4)^4(3x^2y)^2(1/3xy) I did (x^20y^16)(9x^4y^2)(1/3xy) (9x^24y^18)(1/3xy) 3x^25y^19 Is this correct?

More Similar Questions